Child-Friendly Mathematics Learning Model in Islamic Elementary Education: A Case Study at SD At-Taufiqiyah Bangkalan - Yuliana Alfiyatin (BASICA, 2025)
This study aims to formulate a child-friendly mathematics learning model in Islamic elementary education based on the successful practices implemented at SD At-Taufiqiyah Bangkalan. Employing a qualitative instrumental single-case study, the research was conducted from December 2024 to February 2025. Ten informants were selected purposively, comprising the principal, two mathematics teachers, a guidance and counselling teacher, a classroom teacher, and five students. Data were collected through semi-structured interviews, non-participant classroom observations, and document analysis, then examined using reflexive thematic analysis and triangulation. The findings reveal that the model is built upon five interrelated dimensions: ethical-Islamic foundations, contextual and concrete pedagogy, relational and emotional safety, developmental assessment, and distributed institutional support. Islamic values such as rahmah, justice, responsibility, honesty, and mutual assistance were translated into non-violent discipline, respectful communication, differentiated instruction, collaborative learning, constructive responses to errors, and formative feedback. These practices strengthened student participation, confidence, mathematical agency, and conceptual understanding while reducing fear and evaluative pressure. The study concludes that child-friendly mathematics learning functions as an integrated pedagogical ecology rather than a set of isolated techniques, offering an adaptable framework for inclusive, meaningful, and sustainable mathematics education in Islamic elementary schools.